Can compulsory removal ever be justified for adults who are mentally competent?. Issue 4 (December 1991) - Greaves, D A
Abstract : Section 47 of the National Assistance Act is controversial in that it makes provision for the compulsory removal and care of mentally competent adults in certain limited circumstances. A case is described in which it is argued that compulsory management could be justified. This is because the diversity and potentially conflicting nature of the relevant considerations involved in this and a restricted range of other cases, defies their being captured in any wholly rational moral scheme. It follows that if the law is to be both sensitive and just it cannot always provide definitive guidance as to how the community doctor, as the designated decision-maker, should act. The acceptance of his or her judgement is therefore necessary and depends for its proper working on trust, which can only be gained through compassion and respect for the patients concerned.